SEED SUPPLY AND SEED PREFERENCES OF POTATO FARMERS: NIGDE CENTRAL AND IZMIR ODEMİS PROVINCES - M. Çağla ÖRMECİ KART; Canan F. ABAY; Selina GÜNGÖR; Zeynep ÖZER (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present the evolution of Milk Production during the period 1990 -2011 in the North West Region of Potato is one of the most important staple food crops with a significant role for food security and a potential commercial crop in Turkey. As of 2015, Turkey’s potato production amounted to 4.76 million tonnes, and approximately 14.18% of the production occurred in Nigde and 8.57% in Izmir provinces. High-quality seed is the main input for potato production. Import of seed potatoes (rootstock) has increased by 145% and certified seed potato production has increased by 156% in the last 10 years in Turkey. The aim of this study is to determining seed preferences for potato producers in major potato production area, Niğde and İzmir, in Turkey. The study is based on the sample of 141 farmers (69 from the Central district in Nigde and 72 from Odemis district in Izmir) calculated according to the proportional sample size method for 10% error margin and 90% confidential intervals. Conjoint analysis was employed to examine farmers' seed preferences, using seed price, yield, resistance to diseases, production type, maturation time and storage time as the seed attributes. According to the conjoint analysis results, production type has found the first important factor in both research regions such as the cooking type in Nigde, industrial type in Odemis are preferred by farmers. This shows that marketing options affect farmers’ potato seed choices. Disease resistance has found the second important factor in Nigde and third in Odemis after the yield performance when buying seeds.